Psychometric psychopathy: Relationships with indices of reinforcement sensitivity theory factors. (September 2022) - Salgari, Giulia C.; Kramer, Matthew P.; Spencer, Christopher C.; Dvorak, Robert; Bohil, Corey; O'Donnell, John P.; Bedwell, Jeffrey S.
Abstract: The current study examined relationships between psychopathy factor severity and individual differences in reinforcement sensitivity theory factors. Phase 1 examined relationships between factors from the Reinforcement Sensitivity Theory of Personality Questionnaire (RST-PQ) and the two-factor model of psychopathy using the Levenson Self-Report Psychopathy Scale (LSRP) in 2914 undergraduate students (63% women). Multigroup observed variable path analyses revealed unique associations between RST-PQ factors and the two factors of psychopathy. Also, small differences in relationship strength across biological sex were observed. Phase 2 examined the two factors of psychopathy in relation to hedonic ratings from the behavioral Sweet Taste Test (STT), along with self-report measures of trait pleasure, in a subset of participants ( n = 93; 66% women). Analyses revealed robust sex interactions in relationships between STT ratings and the two psychopathy factors. Men with greater secondary psychopathy severity predicted a reduced slope of liking ratings to increasing concentrations of sucrose, while women showed a positive hedonic slope for secondary and a negative hedonic slope for primary psychopathy. Future research should include analyses for possible moderation of sex and incorporate menstrual cycle status in women when examining measures collected in the laboratory. Highlights: Unique associations: reinforcement sensitivity factors and psychopathy facets Differences in relationship strength across biological sex Robust sex interactions in sweet taste test hedonic ratings-to-psychopathy severity Results add knowledge about underlying structure of psychopathy.